2002
DOI: 10.1034/j.1600-0609.2002.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of FISH, RT‐PCR, and RQ‐PCR for monitoring the BCR‐ABL gene after hematopoietic stem cell transplantation in CML

Abstract: The reverse transcriptase-polymerase chain reaction (RT-PCR) was compared with fluorescence in situ hybridization (FISH) and real-time quantitative RT-PCR (RQ-PCR) for minimal residual disease (MRD) monitoring in 266 post-transplant bone marrow samples from 78 patients with chronic myelogenous leukemia (CML). The sensitivities of FISH to BCR-ABL positive samples determined by first-round (1st) RT-PCR, second-round (2nd) RT-PCR, and RQ-PCR were 64.2%, 25.8%, and 20.7%, respectively. The BCR-ABL/ABL ratio by RQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…[8][9][10][11] For patients with CML and APL, techniques for monitoring response to treatment are clinically important to identify, as early as possible, the patients who are at the a high risk of relapse, since some therapeutic approaches such as allogenic bone marrow transplantation may result in long-term disease-free survival. 4,[12][13][14][15] The determination and quantification of residual leukemic cells in patients with CML and APL in remission exposes those who might be at risk of relapse and could require close clinical monitoring. Prognostically valuable structural and numerical chromosomal aberrations may sometimes go undetected by using conventional GTG-banding.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] For patients with CML and APL, techniques for monitoring response to treatment are clinically important to identify, as early as possible, the patients who are at the a high risk of relapse, since some therapeutic approaches such as allogenic bone marrow transplantation may result in long-term disease-free survival. 4,[12][13][14][15] The determination and quantification of residual leukemic cells in patients with CML and APL in remission exposes those who might be at risk of relapse and could require close clinical monitoring. Prognostically valuable structural and numerical chromosomal aberrations may sometimes go undetected by using conventional GTG-banding.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that Q-RT-PCR agreed well with first-round RT-PCR, but not with second-round RT-PCR. 10 Our purpose for defining MRel in the present study was to facilitate decision-making with respect to therapeutic intervention and immunotherapy soon after transplantation, taking into account the risk of severe toxicity, and we used a Q-RT-PCR cut-off level from firstround RT-PCR rather than from second-round RT-PCR. As the cut-off level of Q-RT-PCR for first-round RT-PCR positivity was 0.0189, we arbitrarily defined MRel as a BCR-ABL/ABL ratio exceeding 10 À2 .…”
Section: Definition Of Relapse and Remissionmentioning
confidence: 99%
“…RT-PCR is the most sensitive of the molecular technology-based assays, but it is limited by its qualitative nature, and thus may not detect early relapse in individual patients. On the other hand, Q-RT-PCR correlates strongly with cytogenetics, FISH, RT-PCR, competitive RT-PCR, and Southern blot, [6][7][8][9][10] and its usefulness for MRD monitoring has been reported by many authors. 6,11,12 An important issue when deciding therapeutic intervention using results from Q-RT-PCR is: how should molecular relapse (MRel) be defined and at what level immunotherapy should be given?…”
mentioning
confidence: 99%
“…21,22 To be brief, total RNA was extracted using an RNAqueous Kit (Ambion, Austin, TX, USA) and reverse transcription was performed using 1 mg RNA. The two-step nested procedure was used for the nested RT-PCR amplification (sensitivity, 10…”
Section: Pcr Assaysmentioning
confidence: 99%